Penerapan Prinsip Responsibility Perusahaan Perhotelan Provinsi Bali dalam Pemberian Cuti Tak Berbayar (Unpaid Leave) Pasca Pandemi Covid-19 - Zalza Puti Kamila; Yeti Sumiyati (UNISBA Press, 2023)
Abstract. The principle of responsibility is part of the principles of Good Corporate Governance that must be applied by the company as a form of compliance with laws and regulations in managing company activities. The principle of responsibility makes the company have the obligation to provide humanitarianly decent wages to its employees in accordance with what has been stated in the Employment Agreement and Laws and Regulations. The principle of responsibility for the company is explained through Law Number 40 of 2007 concerning Limited Liability Companies, Law Number 13 of 2003 concerning Manpower, and Law Number 11 of 2020 concerning Job Creation. In circumstances where the company experiences financial difficulties due to the Covid-19 pandemic so that it is unable to provide wages in accordance with the agreement, the company can carry out wage deductions through the provision of unpaid leave by fulfilling the provisions according to Government Regulation Number 36 of 2021 concerning Wages and Decree of the Minister of Manpower Number 104 of 2021 concerning Guidelines for the Implementation of Employment Relations During the Corona Virus Disease Pandemic 2019. But in practice, PT.